The Effect of Group Bibliotherapy in Reducing Social Anxiety of Gifted and Talented Adolescents - Erni Agustina Setiowati; Supra Wimbarti (ANIMA Indonesian Psychological Journal, 2014)
One of the characteristics of gifted adolescents is being oversensitive when interacting with other people and this increases the possibility of feeling anxious in social situation. The purpose of this study is to examine the effectiveness of group bibliotherapy in reducing social anxiety. Participants in this study were five adolescents who have social anxiety problems, with the age range of 11.9 - 13.3 years old and WISC IQ > 130. They had taken part in province and national mathematics competition in the Indonesian Science Olympiad (OSN: Olimpiade Sains Nasional) in 2008 and 2009. A one-group pretest-posttest design was used in this study. The treatment consisted of seven sessions and used Asyik Belajar Matematika 1-6 books that had been rated by three raters. These books contain values related to social issues. The result showed that group bibliotherapy was effective in reducing social anxiety of gifted adolescents. Treatment gains were maintained at a one month follow-up (p = .021, between posttest-pretest and p = .021, between follow up and pretest).